Determinación de sangre oculta con relación al marcador tumoral CA 19-9 en pacientes que acuden al Área de Gastroenterología del hospital del Seguro Social (IESS) - Loja. - Luna Espinoza, Jaime Alberto (2013)
Before the considerable increment of the carcinoma colorectal, so much at world, continental level and in specifically national and local the following study you had carried out to give a contribution of basic importance, which is focused to contribute with the validation of the sensibility and utility of the determination of Ca 19-9 and Hidden Blood in grounds, as routine exams in the prevention and treatment of oncological illnesses at digestive level, also through this work it will be possible to determine that these they are that is to say methods non invasivos that it doesn't involve the use of catheters, previous administration of medications and other means that can represent an external aggression to the patient and with smaller economic cost that you/they will be good to carry out a diagnosis and opportune pursuit of this type of alterations. The present investigation was carried out from a descriptive focus, of traverse type, where the valuation of the marker tumoral CA was made 19-9 and hidden Blood in grounds like a presumptive indicator of carcinoma colorectal in patients that go to the IESS-Loja, the tests of Laboratory they were carried out by the method of quick test of inmunocromatográfica for the detection of hidden blood in fecal matter and ELISA for the quantitative determination of the antigen of the cancer 19-9 (CA 19-9) in human serum, with he/she settled down it an I diagnose presumptive and it guides to diagnose a cancer at level colorectal. The data were obtained of 100 patients that went to the department of Gastroenterología of the IESS-Loja that you/they were inside the inclusion approaches; whose obtained results were, the studied population was of 63% feminine sex and 37 masculine%, the ages are understood from now on of 40 years divided in 3 sections 40-50 years 55%, 56-70 years 26% and bigger to 71 years 19%, 77% presents gastrointestinal problems with presence of hidden blood in grounds and 4% they have the possibility to have a carcinoma at level colorectal with levels superiors to the normal thing in the marker tumoral. Key words: carcinoma colorectal, proves quick of inmunocromatográfica, ELISA, department of Gastroenterología, marker tumoral.